Ahammiyah Ta`līm al-Lughah al-`Arabiyah Laday al-Mubtadi’īn Bi al-Anāsyīd Wa al-Maḥfūẓāt - Mukhlisah Mukhlisah (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
Teaching the Arabic language in the primary stage must take into account their growth in body and mind. The teacher must choose the appropriate materials for them and the methods used to teach them the second language. Otherwise, they should only be taught their mother tongue because they are in the stage of mental and physical development and need to be introduced to basic concepts and the wealth of new vocabulary in their own language. Among the appropriate materials and methods for teaching Arabic as a second language are songs and memorization. One of the most important differences between the two is that songs are pieces of poetry arranged in a specific form, while memorizing pieces may be poetry or prose. Likewise, chants differ from memorization in terms of topics and purposes, as the contents of chants are limited to the emotional and ethical aspects, while the circle of contents of the memorization pieces expands to include, in addition to the emotional and ethical aspects, deep philosophical and mental contents, so it multiplies with the multiplicity of topics in memorization, linguistic purposes and objectives, and others.